2017
DOI: 10.1080/17429145.2017.1370143
|View full text |Cite
|
Sign up to set email alerts
|

Physiological markers of stress susceptibility in maize and triticale under different soil compactions and/or soil water contents

Abstract: Differences between two maize and two triticale genotypes grown in low soil compaction (LSC), moderate soil compaction (MSC) and severe soil compaction (SSC) and with a limited (D) or excess (W) soil water content were observed as a decrease in shoot (S) and root (R) biomass, leaf greening (SPAD) and increase in membrane injury (LI), root and leaf water potential (ψ), photosynthesis (Pn), transpiration (E) and stomata conductance (g S ). Close correlations between ψ L and ψ R, and between differences ψ L and ψ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Responses of different species and cultivars to soil compaction were studied by numerous authors (Colombi & Walter, 2016; Dannowski, 1992; Grzesiak et al., 2017, 2019; Iijima & Kono, 1991; Iijima et al., 1991; Ishaq et al., 2001; Lipiec et al., 1993, 1996; Masle, 2002; Parker et al., 2017). Physiological, morphological and molecular traits were suggested for improving the stress tolerance of crops, and most of them are potentially applicable to maize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses of different species and cultivars to soil compaction were studied by numerous authors (Colombi & Walter, 2016; Dannowski, 1992; Grzesiak et al., 2017, 2019; Iijima & Kono, 1991; Iijima et al., 1991; Ishaq et al., 2001; Lipiec et al., 1993, 1996; Masle, 2002; Parker et al., 2017). Physiological, morphological and molecular traits were suggested for improving the stress tolerance of crops, and most of them are potentially applicable to maize.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments involved 18 maize hybrids selected based on our earlier experiments (Grzesiak et al, 2013(Grzesiak et al, , 2017 and the information received from breeders. Sixteen hybrids were single crosses (SC), and Markiza and Luciana were three line crosses (TC).…”
Section: Plant Materialsmentioning
confidence: 99%
“…However, tolerance to drought stress is a complex feature, and finding suitable phenotypes requires time-consuming exposure of plants to simultaneously or sequentially occurring stress factors in natural conditions. Further, the progress in breeding is slower than expected and some of the reasons are that the genotypic variation in drought tolerance in crops has not yet been fully comprehended [9,[46][47][48], and the genotype itself is not the only factor determining survival in suboptimal conditions [13,14,17,23,33,34,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 20-25% of the global wheat growing area is exposed to drought and the grain yield reduction ranges from 10% to 76% depending on a plant growth stage and a stress severity. Differences in a tolerance to drought within particular genotypes and plant species were proved in many studies, including wheat (Winter et al 1988;Reynolds et al 1998;Paknejad et al 2007), maize (Martinielio and Lorenzoni 1985;Lorens et al 1987;Grzesiak 1990;Grzesiak et al 2012), rape seed (Richards 1978), oat (Larsson and Górny 1988;Marcińska et al 2017), coconut (Gomez et al 2008) and triticale (Royo et al 2000;Grzesiak et al 2012Grzesiak et al , 2017.…”
Section: Introductionmentioning
confidence: 99%